Sistem Pendukung Keputusan Pemilihan Topik Skripsi Program Studi Teknik Informatika Menggunakan Simple Additive Weighting (SAW) - Damayanti Hulu; R Mahdalena Simanjorang (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
The Department of Informatics at STMIK Pelita Nusantara is one of the departments at private universities that focuses on the science of information technology. Thesis problems in this department must also be resolved immediately, one of which is a system that utilizes information technology. It is difficult for students to determine the choice of thesis topic to be prepared as a graduation requirement. There are 7 criteria used, namely: Academic Value, Historical Project, Research Activeness, Training, Interests, Value of Practice and Research Place. Research data obtained from STMIK Pelita Nusantara applied the SAW (Simple Additive Weighting) method using Visual Basic Net 2010 with Mysql Database. From the ranking it shows that the highest result is alternative A1 where in this example the thesis topic chosen is Expert System.